Ship Maneuvering Simulation to Determine Elements of Tugboat Handling: A Case Study of Paciran Port - Fuady, Esqy Dhiya'ul; Asmara, I Putu Sindhu; Sutrisno, Imam (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
Paciran Port, serving as a multipurpose facility for both cargo transport and ferry services, plays a crucial role in the transportation network of East Java province. With a significant increase in vessel visits, particularly barges carrying limestone, ensuring safety during ship berthing operations has become a critical concern. This study aims to identify the key elements of tugboat handling required for safely berthing a barge. The element consists of the percentage of tugboat capacity, the heading of the tugboat, the time series, and the duration. In this study, ship berthing maneuver simulations are based on the Maneuvering Modelling Group (MMG) method. The prediction of the ship's maneuvering motion is simulated using MATLAB software within a 3-DOF (Degree of Freedom) framework. A simulation was conducted across four scenarios by varying the environmental conditions of wind direction, wind speed, current direction, and current speed. Each environmental condition varies into two initial speeds (0 knots and 2.9 knots). The berthing speed limits follow the PIANC standard. The results show that the element of tugboat handling angle can assist the barge to safely berth under diverse environmental conditions and initial speeds, with final berthing speeds consistently below 0.3 m/s (0.58 knots), which falls within the moderate condition category according to PIANC standards. Trajectory analyses further affirmed that the barge remained within the designated Paciran Port channel throughout all simulated scenarios.